2018
DOI: 10.1002/path.5158
|View full text |Cite
|
Sign up to set email alerts
|

Vangl2, a planar cell polarity molecule, is implicated in irreversible and reversible kidney glomerular injury

Abstract: Planar cell polarity (PCP) pathways control the orientation and alignment of epithelial cells within tissues. Van Gogh‐like 2 (Vangl2) is a key PCP protein that is required for the normal differentiation of kidney glomeruli and tubules. Vangl2 has also been implicated in modifying the course of acquired glomerular disease, and here, we further explored how Vangl2 impacts on glomerular pathobiology in this context. Targeted genetic deletion of Vangl2 in mouse glomerular epithelial podocytes enhanced the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 60 publications
5
26
0
Order By: Relevance
“…Surprisingly, heterozygous loss of Vangl2, through the Vangl2 S464N mutation, is sufficient to reduce biliary scarring, suggesting that this system requires tight regulation. Emerging data from other chronically diseased tissues indicate that Wnt-PCP signalling can play a role in the establishment and maintenance of scarring and deposition of the extracellular matrix 20,53,69,70 ; here we show that Wnt-PCP is also involved in the formation of biliary scars in the adult liver.…”
Section: Discussionsupporting
confidence: 62%
“…Surprisingly, heterozygous loss of Vangl2, through the Vangl2 S464N mutation, is sufficient to reduce biliary scarring, suggesting that this system requires tight regulation. Emerging data from other chronically diseased tissues indicate that Wnt-PCP signalling can play a role in the establishment and maintenance of scarring and deposition of the extracellular matrix 20,53,69,70 ; here we show that Wnt-PCP is also involved in the formation of biliary scars in the adult liver.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, downregulation of Vangl2 increased the activity of matrix metalloproteinase-9 (MMP9). MMP9 has previously been shown to be produced by podocytes and it is altered in a number of glomerular diseases, supporting the conclusion that Vangl2 modulates glomerular injury by stopping MMP9 production [48].Therefore, it is possible that TGF-β, lymph angiogenesis and/or Vangl2 could be involved in the development of renal fibrosis and inflammation, thus it could be a key factor in the irreversibility of kidney damage; consequently, additional studies are required to address and demonstrate the involvement of these factors in the reversibility/irreversibility of renal damage, independent of the initial stimulus.…”
Section: Discussionsupporting
confidence: 58%
“…In the kidney, lymph angiogenesis occurs after proteinuria is established and prior to collagen deposition, fibrosis and macrophage infiltration, whereas angiotensin converting enzyme (ACE) inhibition significantly prevents this new lymph vessel formation [45,47]. Papakrivopoulou et al, by analyzing mouse models of irreversible and reversible glomerular injury, described that Van Goghlike 2 (Vangl2), a protein that regulates planar cell polarity (PCP) is implicated in acquired kidney disease by modulating tissue remodeling that includes cytoskeletal rearrangements affecting cell morphology or changes in inflammation [48]. Indeed, downregulation of Vangl2 increased the activity of matrix metalloproteinase-9 (MMP9).…”
Section: Discussionmentioning
confidence: 99%
“…Conserved PCP proteins have further been reported to influence the function of cilia, hence why mutations in PCP genes have been shown to cause ciliopathies ranging from PKD to rarer genetic disorders like MGS, Bardet-Bieldl syndrome and NPHP [80]. It has been shown that Vangl2 is normally expressed in epithelial podocytes that regulate normal differentiation, which later induces the formation of the glomeruli, nephron tubules and collecting duct tubules [81]. Point mutation of Vangl2 in homozygous loop-tail (Lp) mice resulted in malformed kidneys alongside dysmorphic glomeruli [81].…”
Section: Wnt Signalling Receptor Involvement In Ckdmentioning
confidence: 99%